Vertical Up-Scaling and Academic Job Performance in Tertiary Institutions in Calabar Education Zone of Cross River State - Ayang, Ethelbert E. (ALSYSTECH Journal of Education Technology, 2025)
This study investigated the relationship between vertical up-scaling and lecturers’ academic job performance in tertiary institutions within the Calabar Education Zone of Cross River State. Guided by two research questions and two null hypotheses, the study adopted a descriptive survey design and utilized a stratified random sampling technique to select 369 lecturers as respondents. Data were collected using the Questionnaire for Vertical Up-scaling on Academic Job Performance in Tertiary Institutions (QVUSAJP). Responses were analyzed using mean and standard deviation for research questions, while simple linear regression was employed to test the hypotheses at the 0.05 significance level. The findings revealed that professional development opportunities accounted for 33.8% of the variance in academic job performance and had a statistically significant positive influence. Similarly, enhancing research capacities explained 34.8% of the variance and also demonstrated a significant effect on lecturers’ academic job performance. Based on these findings, it was recommended that institutions promote regular workshops, training sessions, and mentorship programs to enhance pedagogical competencies. Furthermore, lecturers should be encouraged to participate in national and international conferences to remain current with global educational and research developments. Future research should extend this study to other regions and explore alternative data collection instruments to enrich understanding of the impact of vertical up-scaling on academic performance.